Analisis Mekanisme Penyusunan Anggaran Belanja Barang dan Belanja Pegawai di Instansi Kepolisian Polrestabes Palembang - Emilia Gustini; Marcelina Angraini (Universitas Katolik Widya Karya Malang, 2025)
In an era of globalization marked by intense competition, effective and efficient budget management is the key to organizational success, including in the law enforcement sector. This study aims to analyze the budgeting mechanism for goods and personnel expenditures within the Greater City Police (Polrestabes) of Palembang. The primary focus of this research is to assess the extent to which the budgeting process is conducted in a structured manner, based on regulations, and aligned with the operational needs of the institution. Based on literature reviews and empirical studies, it was found that the budgeting process at Polrestabes Palembang still faces several challenges, such as delays in data input, limited understanding of performance-based budgeting systems, and weak inter-unit coordination. The complexity of police operational needs, which differ from other civil institutions, requires a specialized budgeting approach. This study adopts a qualitative descriptive approach, utilizing data collection techniques including observation, interviews, and document analysis. The results of this study are expected to contribute to the development of more accountable, transparent, and targeted public budgeting policies, particularly in the security and law enforcement sectors.